Promoting green buildings: Barriers, solutions, and policies - Dina Azhgaliyeva; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2022)
The building and construction sectors contribute about 38% of the greenhouse gas (GHG) emissions and account for 35% of the total energy consumption. With the growing population (especially in developing Asia) and increasing income, the demand for construction and building will continue to rise, which means that GHG emissions from the sector will also rise. Green buildings- encompassing the use of materials and processes which are environmentally friendly and minimizing the use of resources from the design, construction, and maintenance, to demolition stages-have been recognized as an important pathway to mitigate GHG emissions from the construction and building sectors. This paper makes a systematic review of the literature, standards, and policies, and provides a pathway for the implementation of green buildings, particularly in developing countries. The major challenges for green building implementation are access to construction materials and skilled laborers, followed by the high cost of low-carbon construction. Most existing policies provide for energy efficiency in buildings, rather than green buildings. Promoting energy efficiency is not an equal substitute for green building policies, as they do not support the manufacturing of low-carbon construction materials and activities. To reach net-zero carbon emissions and other nationally determined contributions, the construction and building sectors have a tremendous role, which calls for policy support for green buildings.
Keywords: Q28; Q42; Q43; Q53; G2; G3; 330; GHG emission; green building; low-carbon construction; energy-efficiency; NDCs; green building standards